FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN FOOD LOSS AND WASTE (FLW) BEHAVIOR PADA SEKTOR RUMAH TANGGA - Noven, Andreas; Swamilaksita, Prita Dhyani; Harna, Harna; Ronitawati, Putri (Universitas Esa Unggul, 2023)
According to (Bernata, et.al 2020) pandemic conditions affect Indonesian food where there is an increase in food needs because people are encouraged to stay at home, besides that people are unable to get food because most people have to experience termination of employment so they have no income. Conditions during a pandemic like this require public awareness in reducing FLW habits. This study aims to determine the determinant factors that influence the incidence of FLW behavior during the Covid-19 pandemic in the household sector with a cross sectional approach, 100 household managers selected by simple random sampling technique and using correlation analysis. The results of the analysis of the relationship between knowledge p-value (0.004) and R (0.283), age p-value (0.402) and R (-0.085), education p-value (0.017) and R (-0,209), income from work p- value (0.078) and R (-0.177), shopping selection p-value (0.002) and R (0.300), number of family members p-value (0.785) and R (-0.28), choice of meal time p- value (0.001) and R (0.347), and health conditions p-value (0.002) and R (0.309).